Breed-specific differences of gut microbiota and metabolomic insights into fat deposition and meat quality in Chinese Songliao Black Pig and Large White × Landrace Pig Breeds - Suthar Teerath Kumar; Yunpeng Zhang; Qi Zhang; Riaz Muhammad Azeem; Zhang Jing; Li Pan; Wu-Sheng Sun; Yuan Zhao; Shu-Min Zhang (BMC Microbiology)
Abstract Background Gut microbiota ferment non-digestible substances to produce metabolites that accumulate in muscle and influence host metabolism. However, the regulatory mechanisms connecting gut microbiota, metabolites, and fat deposition across pig breeds remain unclear. This study explores the gut–muscle axis regulating fat deposition and meat quality in Chinese Songliao Black Pig (SBP) and Large White × Landrace Pigs (LWLDP). Digesta samples from the ileum, cecum, and rectum of both breeds were analyzed using 16 S rRNA sequencing for microbiome profiling and ultra-high-performance liquid chromatography (UHPLC) for metabolomics. Multi-omics data, including microbiota and metabolite profiles were integrated with our previously published data of transcriptomics and metabolomics insights into fat deposition in the longissimus dorsi (LD) muscle using the MixOmics DIABLO method. Results Microbiome analysis revealed that Fibrobacter, Unidentified_Peptostreptococcaceae, Sutterella, and Unidentifed_Rickettsiales were enriched in SBP, while Ruminococcus, Corynebacterium, and Streptococcaceae in LWLDP. Metabolomic analysis indicated that SBP was enriched in fatty acid biosynthesis pathways, including linoleic acid, α-linolenic acid, and arachidonic acid, whereas LWLDP was associated with insulin signaling, starch and sucrose metabolism. Integrated analysis identified Peptostreptococcaceae and Rickettsiales in SBP, along with metabolites phosphatidylcholine (PC(22:4)), N-acylethanolamine (NAE(20:4)), and lysophosphatidylcholine (LysoPC(24:1)) were correlated with key genes (EIF4E, MSTN, PPARGC1A, NR4A3, and SOCS1) regulating fat deposition. In LWLDP, Corynebacterium and Streptococcaceae were linked to the PPP1R3B gene, which is involved in glycogen metabolism, as well as metabolites 2-methyl-3-hydroxybutyric acid and 5-keto-gluconic acid, suggesting a shift toward glycolysis over lipolysis. Conclusion This study concluded that cecum-associated microbes in LWLDP may enhance carbohydrate metabolism, leading to reduced fat deposition, whereas rectum-associated microbes in SBP contribute to docosahexaenoic acid (DHA) biosynthesis, thereby improving meat quality. These findings highlight gut microbiota-derived metabolites as potential biomarkers for optimizing meat production and livestock breeding strategies.